Injection Sclerotherapy with 5% Phenol in Almond Oil in the Treatment of Rectal Prolapse in Children: Our Experience - Hoque, Md Mozammel; Ahmed, Alauddin; Nandy, Alak (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Rectal prolapse is a relatively common condition in children. A wide variety of sclerosing agents have been used in the treatment of rectal prolapse in children. We have used 5 % phenol in almond oil in the treatment of rectal prolapse in our children. The aim of this study was to find out the outcome of injection sclerotherapy with 5% phenol in almond oil in the treatment of rectal prolapse in children. Methods: From May 2009 to December 2016 a total of 186 patients with rectal prolapse were treated by injection sclerotherapy with 5% phenol in almond oil. Of which males were 112 and females 74. Age ranged from 1.5 years to 7 years. Initial management included assessment and correction of predisposing factors. If the rectal prolapse persisted or if the prolapse required repeated reduction, injection sclerotherapy was performed. Number of injections, recurrences, and complications were reviewed. Results: Out of 186 patients recurrence occurred in 12 patients, cured after second injection in 10 patients and 2 children needs Thiersch’s stitch. Excessive oozing at the injection site was in 5 patients. Conclusion: Injection sclerotherapy with 5% phenol in almond oil is simple, safe and effective treatment of recurrent rectal prolapse after failure to conservative measures. Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 19-21